Contrasting species and functional beta diversity in montane ant assemblages. (16th May 2015) - Bishop, Tom R.; Robertson, Mark P.; van Rensburg, Berndt J.; Parr, Catherine L.
Abstract Aim Beta diversity describes the variation in species composition between sites and can be used to infer why different species occupy different parts of the globe. It can be viewed in a number of ways. First, it can be partitioned into two distinct patterns: turnover and nestedness. Second, it can be investigated from either a species identity or a functional‐trait point of view. We aim to document for the first time how these two aspects of beta diversity vary in response to a large environmental gradient. Location Maloti‐Drakensberg Mountains, southern Africa. Methods We sampled ant assemblages along an extensive elevational gradient (900–3000 m a.s.l.) twice yearly for 7 years, and collected functional‐trait information related to the species' dietary and habitat‐structure preferences. We used recently developed methods to partition species and functional beta diversity into their turnover and nestedness components. A series of null models were used to test whether the observed beta diversity patterns differed from random expectations. Results Species beta diversity was driven by turnover, but functional beta diversity was composed of both turnover and nestedness patterns at different parts of the gradient. Null models revealed that deterministic processes were likely to be responsible for the species patterns but that the functional changes were indistinguishable from stochasticity. Main conclusions Different ant species are found with increasing elevation, but they tend to represent an increasingly nested subset of the available functional strategies. This finding is unique and narrows down the list of possible factors that control ant existence across elevation. We conclude that diet and habitat preferences have little role in structuring ant assemblages in montane environments and that some other factor must be driving the non‐random patterns of species turnover. This finding also highlights the importance of distinguishing between different kinds of beta diversity.